An assessment of water re-use and feed on the growth performance of tilapia and pond water quality - Obeng, Philomena (2014)
A Thesis submitted to the Department of Freshwater Fisheries and Watershed Management, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of philosophy in Aquaculture, October-2012